Impact of Aging, Cytomegalovirus Infection, and Long-Term Treatment for Human Immunodeficiency Virus on CD8+ T-Cell Subsets - Veel, Ellen; Westera, Liset; van Gent, Rogier; Bont, Louis; Otto, Sigrid; Ruijsink, Bram; Rabouw, Huib H.; Mudrikova, Tania; Wensing, Annemarie; Hoepelman, Andy I. M.; Borghans, José A. M.; Tesselaar, Kiki (Frontiers in Immunology, 2018)
Both healthy ageing and HIV-infection lead to a progressive decline in naive CD8+ T-cell numbers and expansion of the CD8+ T-cell memory and effector compartments. HIV-infection is therefore often considered a condition of premature ageing. Total CD8+ T-cell numbers of HIV-infected individuals typically stay increased even after long-term combination anti-retroviral treatment (cART), which is associated with an increased risk of non-AIDS morbidity and mortality. The causes of these persistent changes in the CD8+ T-cell pool remain debated. Here we studied the impact of age, CMV infection and long-term successful cART on absolute cell numbers in different CD8+ T-cell subsets. While naive CD8+ T-cell numbers in cART-treated individuals (N=38) increased to healthy levels, central memory (CM), effector memory (EM) and effector CD8+ T-cell numbers remained higher than in (unselected) age-matched healthy controls (N=107). Longitudinal analysis in a subset of patients showed that cART did result in a loss of memory CD8+ T cells, mainly during the first year of cART, after which memory cell numbers remained relatively stable. As CMV infection is known to increase CD8+ T-cell numbers in healthy individuals, we studied whether any of the persistent changes in the CD8+ T-cell pools of cART-treated patients could be a direct reflection of the high CMV prevalence among HIV-infected individuals. We found that EM and effector CD8+ T-cell numbers in CMV+ healthy individuals (N=87) were significantly higher than in CMV- (N=170) healthy individuals. As a result, EM and effector CD8+ T-cell numbers in successfully cART-treated HIV-infected individuals did not deviate significantly from those of age-matched CMV+ healthy controls (N=39). In contrast, CM T-cell numbers were quite similar in CMV+ and CMV- healthy individuals across all ages. The long-term expansion of the CM CD8+ T-cell pool in cART-treated individuals could thus not be attributed directly to CMV, and was also not related to residual HIV RNA or to the presence of HIV-specific CM T cells. It remains to be investigated why the CM CD8+ T-cell subset shows seemingly irreversible changes despite years of effective treatment.